PERCEPTION OF EXTERNAL STAKEHOLDERS ON THE AVAILABILITY OF THE LACTATION CORNER ACCORDING TO THE REGULATION OF THE MINISTER OF HEALTH NO 15/2013 CONCERNING THE PROVISION OF SPECIAL FACILITIES FOR BREASTFEEDING IN THE MALL OF TEGAL CITY - Evi Zulfiana; Seventina Nurul Hidayah (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2020)
Based on the Regulation of the Ministry of Health No. 15/2013, an institution or public places must provide particular facilities for breastfeeding mothers. Therefore, stakeholders must be able to guarantee the availability of space for the comfort and freedom of mothers in breastfeeding their children. The purpose of this study was to determine the perceptions of external stakeholders about the existence, constraints, and lactation corner policies. This study was qualitative. Data retrieval was carried out with in-depth interview techniques using interview guidelines. The results of the information obtained were recorded. The data obtained validated using source triangulation. The results of this study found that all respondents had perceptions about breast milk and lactation corners correctly. Constraints on the use of lactation corners found that there was no refrigerator in the mall. The majority of respondents do not understand that there was a policy that regulates the existence of the lactation corner; it was due to the lack of socialization to stakeholders from related parties. Keyword: Breastfeeding, Lactation Corner, mall, stakeholders